(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2023)
Due to the impact of the COVID-19 pandemic, destinations are facing the crisis of losing benefits, tourists and reputations, and the negative evaluations of destination performances. Trust is an important variable which has been used in crisis management and destination development. Moreover, destination trust can be used as an effective tool to increase tourists’ travel intention and revitalize tourism after the COVID-19. However, limited studies have examined the role of destination trust in tourists’ travel decision after the pandemic. The purpose of this study was to explore antecedents of destination trust from cognitive perspective and to examine the role of destination trust in tourists’ travel behaviors after the COVID-19 pandemic. Data was collected through a self-administered questionnaire from Mainland Chinese tourists who plan to travel to Macau after the pandemic in May and June 2022. The results showed that destination trust was influenced by destination image, destination reputation and knowledge of government performance. Destination image and reputation were important antecedents of travel intention. Destination reputation had the strongest impact on destination trust and travel intention. This study extends the existing literature and provides a new conceptual framework to examine travel intention by emphasizing the effect of destination trust. From practical implications, this study provides suggestions to destinations to deal with crisis caused by the pandemic, and to facilitate the recovery of tourism industry. Destination managers should provide satisfying performances, and rebuild strong destination images and reputation to increase tourists’ trust of destination and travel intention after the COVID-19.